A não linearidade entre a reação de quem copia e de quem é copiado - Watanabe, Edson H. (Estudos Avançados, 2014)
This article offers an account of experiences related to the problem of third-party copyright infringement, as well as some measures adopted by Coppe (the Alberto Luiz Coimbra Institute for Graduate Studies and Research in Engineering, at Rio de Janeiro Federal University) to curb potential problems in this area, including formal and educational measures. The title suggests that the issue is still poorly understood among undergraduate and graduate students (and professors), and that a wholly nonlinear reaction is common between those who copy or those who are copied. We end the article with some suggestions on measures that could be adopted to eliminate (minimize) problems of plagiarism and raise awareness on matters of integrity in research.